2021
DOI: 10.3390/ijerph18020653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on the Skin Epithelial Barrier of Young Elite Athletes-Swimming Comparatively to Non-Water Sports Training Session

Abstract: The benefits of swimming have been extensively assessed. However, swimming pools contain chlorine and other irritating chemicals that may induce contact dermatitis. To evaluate the effect of a swimming training session on transepidermal water loss (TWEL) in swimmers compared to football players, elite swimmers and football players were invited to participate (58 athletes) in the study, where TEWL was measured before, immediately after, and 30 min after a 2 h training session. The probe was held on the dorsum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 8 One study in elite teenage swimmers without AD has shown TEWL increases immediately following 2 h of intensive swimming training, but returns to normal after 30 min. 9 However, most children are unlikely to spend 2 h in the pool, and TEWL rapidly returns to normal levels after submersion, which is reassuring.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… 8 One study in elite teenage swimmers without AD has shown TEWL increases immediately following 2 h of intensive swimming training, but returns to normal after 30 min. 9 However, most children are unlikely to spend 2 h in the pool, and TEWL rapidly returns to normal levels after submersion, which is reassuring.…”
Section: Resultsmentioning
confidence: 97%
“…Transepidermal water loss (TEWL) is a surrogate marker for skin barrier function, and aberrations in TEWL are known to predate the clinical development of AD 8 . One study in elite teenage swimmers without AD has shown TEWL increases immediately following 2 h of intensive swimming training, but returns to normal after 30 min 9 . However, most children are unlikely to spend 2 h in the pool, and TEWL rapidly returns to normal levels after submersion, which is reassuring.…”
Section: Resultsmentioning
confidence: 99%
“…Other work also mainly focuses on the analysis of swimmers themselves [ 18 ] or the swimming environment [ 19 ]. Other works analyze a part, such as the arms [ 20 ] or skin [ 21 ]. Although everyone has contributed a lot of work in this field, no one has conducted a coherent study from the external macro perspective to the micro perspective of the action details.…”
Section: Introductionmentioning
confidence: 99%